Contribution of Civil Society Organizations to Womenâ€™s Political Participation in Ethiopia: The Case of Amhara Women’s Association - Dessie, Mulunesh; Demissie, Sewmehon (Ethiopian Journal of Social Sciences, 2023)
It is crucial that Civil Society Organizations (CSOs) connect the government to the public and fill gaps in the policies of governments in a wide range of dimensions. They have been advocating for citizens’ rights, including gender equality (GE), through lobbying government institutions and society, exposing government weaknesses, and promoting democratic values. Thus, this study assessed the experience of the Amhara Womenâ€™s Association (AWA) and its contribution to enhancing women’s political participation and gender equality. The study used a case study design and a qualitative research approach. Data was gathered from primary and secondary sources via key informant interviews and document analysis. The main data, which was largely gathered through interviews, was analysed using thematic analysis. The study included 18 key informants (the chairperson of the Amhara Women’s Association, members and experts from BOWCYA, and CSOs). The result of the study shows that AWA seeks to play a vital role in promoting gender equality and democracy in the region. This is done by encouraging and empowering women to be active participants and beneficiaries of the country’s leadership and democratization process. Despite this, the organization has faced several challenges such as its lack of independence, budgetary constraints, the overlap of duties and rights and government interference. Furthermore, it is crucial to increase the political commitment to empowering women to be active participants in politics. The goal is to enable CSOs to participate more effectively and efficiently by strengthening and/or establishing independent and autonomous organizations. Accordingly, a review of CSO law in 2019 opens up the political arena.